2022
DOI: 10.1038/s41598-022-17569-2
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of public facilities between urban and rural areas and its driving factors in ten cities of China

Abstract: Urban development continues to face the dilemma of spatial inequality of public facilities, particularly educational and medical facilities. Identifying inequalities in various types of public facilities and their driving mechanisms is crucial in reducing social inequality. However, information on this topic is limited. This study took 10 typical cities in China as cases. We used the methods of the Gini coefficient and hedonic price model as bases in evaluating the equality of nine types of education and medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…In contrast, recent policies have markedly enhanced medical infrastructure in rural settings and equalized access to healthcare across different SES demographics. 26 , 27 Another explanation is that a larger proportion of OPA in urban setting belongs to the MPA as opposed to the VPA. Our explorative analysis and previous research demonstrated that VPA is more closely associated with mortality than MPA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent policies have markedly enhanced medical infrastructure in rural settings and equalized access to healthcare across different SES demographics. 26 , 27 Another explanation is that a larger proportion of OPA in urban setting belongs to the MPA as opposed to the VPA. Our explorative analysis and previous research demonstrated that VPA is more closely associated with mortality than MPA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent policies have substantially improved rural medical infrastructures. 40 , 41 , 42 Such advancements might have equalized medical access across educational strata in rural settings. According to the health statistics yearbook, in 2019, the number of medical institutions in rural areas reached 795,534, while 212,045 in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…These small towns should evolve into socio-economic centers and urbanrural links in rural areas, promoting the coordinated development of urban and rural areas within urban agglomerations. Additionally, from a "People" perspective, initial urban agglomeration construction should consider regional development characteristics, improving the public service supply mechanism for equal access to urban and rural public services 29 . This, in turn, would facilitate the urbanization of migrant workers, drive rural modernization, and comprehensively promote the integrated development of regional urban and rural areas 30 .…”
Section: Discussionmentioning
confidence: 99%